Massive cutaneous fistula secondary to an odontogenic submandibular abcess in an immunocompromised patient: a case report - Aydin Gulses; Gurkan Bayar; Kemal Simsek; Tamer Zerener; Yavuz Aydintug (Cumhuriyet University, 2014)
Extraoral sinus tracts of dental origin often are a diagnostic challenge. A delay in correctly diagnosing these types of lesions can result in ineffective and inappropriate treatment. A 64 year-old immunocompromised female with a huge cutaneous draining tract was referred to our clinic complaining of a purulent discharge from her skin on her right submandibular area. In clinical examination and radiographic assessment, periapical lesion associated with roots of lower right first molar was noticed. According to the patient history, she had kidney transplantation 17 years ago. Following the identification of the source of infection, it was surgically and medically resolved, and skin closure was performed. Her postoperative healing period was supported with hyperbaric oxygen therapy as well. Sinus tract was successfully treated.